A Foucauldian discourse analysis of sexual harassment in Greek academic community - Kiriazopoulou , Aggeliki; Athanasiadis , Kimon; Iliopoulou , Triantafyllia (Social Cohesion and Development, 2023)
This research investigates the views and perspectives of Greek undergraduate students upon sexual harassment in academic community. The sample was 6 students and the dat were analysed with the use of the Foucauldian Discourse Analysis. Four main themes emerged from the analysis: The “gen-der blind” vulnerability discourse, the power as a driving force, patriarchy as a developmental factor for the male perpetrator and power relations in the academic community. Patriarchy constitutes a developmental factor for the male perpetrator thus moralising practices and behaviours that develop fear and a culture of silence. Regarding the academic community, power relations are built on the concepts of prestige, profit and on the high ranking position thus interpreting power relations as gender relations.